Gypsy law – the non-state normative orders of Roma: scholarly debates and the Scandinavian knowledge chasm. Issue 1 (2nd January 2016) - Nafstad, Ida
Abstract: The Rom legal culture and applied normative orders vary between different Rom communities, and are often divided into two main practices, i.e. tribunals and private solutions. The main form of tribunals is the so-called Kris, while the foremost private solution is the feud. In practice, Gypsy law can be seen as pragmatic, where any means suitable is used to resolve a conflict or to address an unwanted incident. The aims of this paper are to give an updated overview of the research on Gypsy law, to outline the main debates in the area, and to identify some important gaps in order to deepen the knowledge on Gypsy law and the relations between Rom communities and mainstream societies. The overview identifies and elaborates on three main trends in the research on Gypsy law: (1) anthropology of Rom life and culture; (2) Gypsy law legal studies; and (3) contemporary issues in Gypsy law studies. Furthermore, the paper discusses what we know and can know about Scandinavian Gypsy law. The literature on Gypsy law in Scandinavia is almost non-existent. Legal pluralism researchers have not paid much attention neither to Gypsy law in general nor in relation to the vast amount of research on non-state law in post-colonial situations and in countries of the South. The non-state parallel legal system of Gypsy law, existing in the midst of the Western world, is getting scarce attention. It is hence of importance to direct attention to, and provide an overview of knowledge about, this non-state legal system.